Induction of PR-proteins and defense related enzymes in black pepper due to inoculation with Phytophthora capsici - M. ANANDARAJ; Y.R. SARMA, R. STEPHEN JEBAKUMAR, (Indian Phytopathology, 2002)
The activities of phenylalanine ammonia lyase (PAL) and 61,3 glucanase in both leaf and root tissues of three black pepper varieties (tolerant P24; and susceptible Panniyur! and Subhakara) were determined in healthy and Phytophthora capsici infected tissues. Infection generally enhanced both of these enzyme activities. SDS-PAGE study revealed the induction of PR-proteins in the infected tissues. Western blotting with anti-tobacco 61,3 glucanase antibody confirmed the presence of these isoforms in the leaf extract. Among the three varieties studied, the Phytophthora tolerant P24 expressed higher rate of these defense-related enzymes/proteins.